A Study of the Psychometric Characteristics of the Renzulli Scale to Identify Gifted Students in the Primary Stage in As-Suwayda Province - Hodaifa, Riham Solaiman (Journal of Educational and Psychological Sciences, 2022)
This research aims at exploring the identification and diagnostic methods of gifted pupils at the primary stage in As-Suwayda Province, through developing a Syrian image of the Renzulli Scale, which has indications of validity, stability, and effectiveness of the Syrian environment characteristics, in order to identify gifted students at this stage. The development of a Syrian image of the Renzulli Scale includes a number of stages and procedures; adopting the Jordanian image of the Scale (Surour, 1989), and reviewing it by a number of judging academics in the Department of Special Education and Educational and Psychological Measurement and Evaluation. The adopted image is then applied to a sample of 100 male and female pupils representing a number of primary school students in As-Suwayda Governorate, whose nomination was made by teachers. The acquired data is then analysed in order to find the indicators of discriminatory validity, which in turn showed that the difference is in favour of the first group (higher), whose average is greater than the mean of the second group (lower) in the areas of the Renzulli scale. This demonstrates that the Scale is characterised by a discriminatory ability in favour of the higher group in the total score of the scale. The validity of the inter-correlations is investigated and it shows that the correlation coefficients of the Scale’s items, and the correlation coefficients between the Scale’s domains are both of a significant level of 0.01. The verbal validity is also investigated using another study (the Stanford-Binet test, short edition, 5th version) codified on the Syrian environment. It shows that the values ​​of the correlation of the verbal knowledge test with the domains of the Renzulli Scale and its total score ranged between (0.742-0.297), whereas the values ​​of the correlation with the matrices test ranged between (0.695-0.294). As for the Scale stability indicators, they are determined using two methods; namely, the recurrence method, where the reliability coefficients ranged between 0.882 and 0.794; and the Cronbach’s Alpha method, where the reliability coefficients ranged between 0.878 and 0.801.